Effects of simvastatin pretreatment on clomiphene response in clomiphene - resistant women with polycystic ovary syndrome. - Azam Azargoon; Raheb Ghorbani; Zahra Faraji (Tehran University of Medical Sciences, 2013)
Objective: The aim of this study is to determine if simvastatin pretreatment would change clomiphene response in clomiphene citrate-resistant (CC-R)women with (PCOS). Materials and methods: This quasi experimental study included twenty five clomiphene resistant women with PCOS. All patients received cyclic oral contraceptives pills (OCP) (30µg of ethinyl estradiol and 150µg of desogestrol) from the 5th day of their spontaneous or progesterone (P) induced menstrual cycle; in addition, they received simvastatin (20mg/day) from the first day of cycle for two consecutive months. Then, patients were given 100 mg clomiphene citrate (CC) (Iran Hormone, Iran) for five days starting from day three of their menstrual cycles. The primary outcome measures were ovulation and pregnancy rates. The change in body mass index (BMI), the mean number of follicles ≥ 18 mm, the mean of follicular size and endometrial thickness on the day of human chorionic gonadotropin (HCG) administration were secondary outcome measures. Results: Ovulation occurred in 5 out of 25 (20%) patients, but none of the patients conceived in this study. No important change in BMI was observed after using simvastatin (0.28 + 1.13; p = 0.228). In all patients with ovulation, the number of follicles ≥ 18mm was one. The mean follicular size and endometrial thickness on the day of HCG administration were 19.67 ± 2.04 and 7.00 ± 1.34, respectively. Conclusion: In this study, we did not observe the favorable effect on ovulation and pregnancy rates with CC following of simvastatin pretreatment in CC-resistant PCOS women. So, further studies with a larger number of patients, higher doses of CC and more cycles are necessary to make this obvious.